The Role of Leadership in Educational Supervision: A Literature Reviews on Improving Teacher Performance and Learning Outcomes at Islamic Senior High School 1 Bukittinggi - Nasrul, Nasrul; Gistituati, Nurhizrah; Anisah, Anisah (International Journal of Educational Dynamics, 2024)
The primary aim of this article is to enhance readers' understanding of the leadership roles of educational supervisors. It explores the challenges and issues they face in performing their duties, examines the factors influencing their performance, and proposes recommendations to improve their effectiveness. A qualitative methodology was employed, involving literature reviews and field observations at Islamic Senior High School 1 Bukittinggi. The study highlights the effectiveness of transformational, collaborative, and participatory leadership styles in educational supervision. Results indicate that these styles improve teacher motivation, organizational commitment, and the quality of the teaching-learning process. Additionally, supervision methods leveraging technology, such as AVOS-based CCTV systems, were found to enhance monitoring and feedback mechanisms while minimizing classroom disruptions. Despite the advantages, challenges such as limited resources, technical issues, and resistance to change remain. The findings underscore the importance of continuous training, robust evaluation systems, and strong support from superiors in enhancing supervisory performance. Effective leadership in educational supervision is characterized by clear communication, a shared vision, and proactive support for teachers and students. This study concludes that adopting innovative supervision approaches and effective leadership styles can significantly improve educational quality.